The traditional media, political parallelism and public opinion on contentious issues in the 2018 Italian election campaign. Issue 3 (2nd September 2018) - Roncarolo, Franca; Mancini, Paolo
ABSTRACT: This article derives from a survey research and a content analysis of traditional media, in the 2018 Italian election campaign. In the first part, traditional Italian news media partisanhip is discussed as findings demonstrate that it still alive in-spite of novelties deriving from the development of new media. In the second part, authors investigate the level of negativity of news stories and how it is linked to different habits of consumption and different political affiliations of viewers and readers. Findings demonstrate that at the basis of the electoral result, which deeply modified the previous political landscape, there was a climate of opinion that was influenced by the way news media treated contentious issues such as immigration and Europe.